ADVANCING LIGHTWEIGHT CONCRETE: EXPERIMENTAL STUDY WITH OIL PALM KERNEL SHELL AS COARSE AGGREGATE AND BINDER SUBSTITUTE - Suresh, Bhukya.; Abdulmuneer, Md.; Ramu, Guguloth.; Navya, Jetti. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
One of the most basic needs for human survival is a safe refuge. Sadly, during the course of this century, adequate housing for the great majority of the homeless has not appeared. The high price of concrete materials has drawn criticism from the public and has affected both construction and civil engineering projects. Research on genetic local resources that are discarded into our environment as trash and result in pollution and traffic congestion has been conducted as an alternative material as a result of these and other factors. Consequently, an investigation was conducted to ascertain the feasibility of substituting some of the coarse aggregate in concrete with palm kernel shell. A kind of biosolid waste called oil palm kernel shell, or OPKS, is created as a byproduct of the palm oil industry in tropical nations. Concrete may include this trash as an aggregate. For research purposes, OPKS has been used as a natural lightweight aggregate (LWC) in the manufacturing of lightweight concrete since 1984. In this research, normal weight concrete (NWC) of equivalent strength is compared with the fresh, mechanical, and bond qualities of grade M30 lightweight concrete, namely oil palm kernel shell concrete (OPKSC). Oil palm kernel shell (OPKS), an industrial waste, has been transformed into lightweight aggregates (LWA) by the Oil Palm Kernel Shell Committee (OPKSC). Flyash was employed as a preferred binding material replacement at a constant percentage of 5% for all combinations of mix proportions of ten percent, twenty percent, thirty percent, and forty percent oil palm kernel shell partial substitution of course aggregate. Compared to the NWC, the OPKSC produced a density decrease of around 20%.